The Strategic Role of the Indonesian FDA in Empowering Micro, Small, and Medium Enterprises in the Drug and Food Sectors: A Review - Kashuri, Mohamad; Ikrar, Taruna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This review examines the evolving role of the Indonesian Food and Drug Authority (BPOM) in empowering Small and Medium Enterprises (SMEs) within the pharmaceutical and food sectors. While significant strides have been made in recent years, challenges remain. These include discrepancies between regulatory objectives and the practical capabilities of SMEs, particularly in navigating complex regulatory frameworks. While digitalization initiatives and technical assistance programs have shown promise, their impact is often hindered by resource limitations and resistance to change among stakeholders. This review underscores the critical need for a balanced approach that effectively integrates regulatory oversight with targeted support for SME growth. Fostering an ecosystem that encourages innovation and ensures regulatory compliance necessitates a multi-stakeholder approach, demanding more sustainable and effective coordination among government agencies, industry associations, and academic institutions. The success of BPOM's empowerment efforts hinges on adopting flexible, technology-driven, and results-oriented strategies. Future endeavors should prioritize long-term evaluations of existing programs, develop robust metrics to assess their effectiveness and explore innovative approaches to address the evolving regulatory landscape in the digital era.